Epidemiological survival predictors of cancer of the corpus uteri: a population-based analysis - A. V. Svetlakova; D. D. Gromov; O. V. Chemakina; A. V. Agayeva; L. E. Valkova; A. A. Dyachenko; D. V. Bogdanov; M. Yu. Valkov (Сибирский онкологический журнал)
Cancer of the corpus uteri (CCU) is one of the most common gynecological malignancies in high- and middleincome countries. The objective of the study was to evaluate the factors predicting survival in CCU patients over the period 2000-2021 using the data of population-based cancer registry of the Arkhangelsk region. Material and Methods. Cancer-specific survival (CSS) of patients with CCU for the period 2000-21 was evaluated using life tables and Kaplan-Mayer methods with a log-rank test. The Cox proportional hazards regression model was used to assess the effect of prognostic factors on survival time. Results. A total of 3272 cases were selected for the analysis. The 5-year survival rates improved from 70.6 % in 2000-04 to 75.6 % in 2015-19. In stage I, II, III, and IV CUN, the 5-year survival rates were 90.8 % (95 % CI 89.3-92.0 %), 71.1 (95 % CI 66.3-75.4 %), 46.7 (95 % CI 41.4-51.8 %), and 3.9 (95 % CI 1.5-7.5 %), respectively; p<0.001. In the multivariate regression model, for stage II, III, and IV CCU, the hazard ratios for death from cancer were respectively 2.69 (2.14-3.39), 5.73 (4.66-7.03), and 20.26 (16.13-25.44) compared to stage I. The risk of death from CCU was 2.0-2.7 times higher in patients with aggressive histological subtypes and sarcomas compared to that in patients with endometrioid adenocarcinoma; 2.0-2.8 times higher in patients older than 60 years compared to younger patients, and 1.3 times higher in rural patients compared to urban patients (p<0.05). There was no increase in the risk of death from CCU over the period of COVID-19 pandemic. Conclusion. In this population-based study, we have found that the survival of patients with CCU is significantly affected by age and place of residence, which may indicate a limited access of some patients to effective treatment and requires further analysis. No increased risk of death from CCU during the COVID-19 pandemic was found.